Nerve transfer from the median to musculocutaneous nerve to induce active elbow flexion in selected cases of arthrogryposis multiplex congenita. Issue 8 (19th March 2019) - Hagemann, Christian; Stücker, Ralf; Breyer, Sandra; Kunkel, Philip O. S.
Abstract : Background: Arthrogryposis multiplex congenita (AMC) is a rare disease which affects mainly upper and lower extremities. Affected patients are not able to eat unassisted due to elbow contracture and nonexistent active elbow flexion. In traumatic brachial plexus palsies, a nerve transfer from either median or ulnar nerve to the musculocutaneous nerve has proved to induce active elbow flexion, and we report our results of such a procedure in a nontraumatic condition, that is, arthrogryposis. Methods: We selected four patients with AMC type 1 (6 extremities, 2 males, 2 females) diagnosed with AMC presenting to our institution shortly after birth from 2014 to 2016 to perform a nerve transfer from the median nerve to the musculocutaneous nerve in order to induce active elbow flexion. The indication of application of this surgical procedure was based on active finger and wrist flexion, limited contracture of elbow joints and evidence of flexing muscle fibers detected by sonography. Results: Five nerve transfers were conducted with a follow up of 2–5 years. Two extremities reached active elbow flexion motorgrade M4, two M3, and one M1 at latest follow up. One patient developed a postoperative suture granuloma. One nerve transfer was abandoned due to neuroanatomic variation. One extremity was treated with botulinum toxin in triceps muscle in addition to the nerve transfer. Conclusions: In this series of selected cases of AMC Type 1 we were able to induce active elbow flexion using a nerve transfer technique developed for traumatic and obstetric brachial plexus palsies. In four extremities the procedure achieved independent hand‐to‐mouth active elbow flexion. Level of evidence four.